2012
DOI: 10.1155/2012/751683
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyositis Sine Myositis with Membranoproliferative Glomerulonephritis

Abstract: Dermatomyositis (DM) is an autoimmune disease that is characterized by involvement of proximal musculature and skin. We report a 52-year-old woman with a 6-year history of dermatomyositis sine myositis, who developed lower extremity edema and proteinuria. Pathological examination of renal biopsy showed membranoproliferative glomerulonephritis. She received steroid, cyclophosphamide, and mycophenolate mofetil. Over the 9 to 10 months after the beginning of treatment, the proteinuria was improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…As for the study by Couvrat-Desvergnes et al, they identified 14 patients who had undergone renal biopsy (6 PM, 5 DM, and 3 ASS), which revealed the presence of glomerulonephritis with various pathologic patterns including immune complex-related glomerulonephritis (n � 4), membranous nephropathy (n � 2), and IgA nephropathy (n � 2) [5]. We conducted an additional literature search and retrieved case reports describing the association of PM or DM with a variety of pathological glomerular lesions, including mesangial proliferative glomerulonephritis [21][22][23][24][25], membranous nephropathy [26][27][28][29][30][31], membranoproliferative glomerulonephritis [32], IgA nephropathy [33][34][35][36][37], diffuse proliferative glomerulonephritis [38], immune complex-type glomerulonephritis [39][40][41][42], acute interstitial nephritis [43], lipoid nephrosis and focal glomerulosclerosis [44], focal segmental glomerulosclerosis with evidence of acute tubular injury [45], sclerotic GN with fibrocellular crescent [46], and crescentic glomerulonephritis associated with malignancy [47]. Cases presenting with anti-neutrophil cytoplasmic antibody-associated glomerulonephritis in the context of DM have also been reported [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…As for the study by Couvrat-Desvergnes et al, they identified 14 patients who had undergone renal biopsy (6 PM, 5 DM, and 3 ASS), which revealed the presence of glomerulonephritis with various pathologic patterns including immune complex-related glomerulonephritis (n � 4), membranous nephropathy (n � 2), and IgA nephropathy (n � 2) [5]. We conducted an additional literature search and retrieved case reports describing the association of PM or DM with a variety of pathological glomerular lesions, including mesangial proliferative glomerulonephritis [21][22][23][24][25], membranous nephropathy [26][27][28][29][30][31], membranoproliferative glomerulonephritis [32], IgA nephropathy [33][34][35][36][37], diffuse proliferative glomerulonephritis [38], immune complex-type glomerulonephritis [39][40][41][42], acute interstitial nephritis [43], lipoid nephrosis and focal glomerulosclerosis [44], focal segmental glomerulosclerosis with evidence of acute tubular injury [45], sclerotic GN with fibrocellular crescent [46], and crescentic glomerulonephritis associated with malignancy [47]. Cases presenting with anti-neutrophil cytoplasmic antibody-associated glomerulonephritis in the context of DM have also been reported [48][49][50].…”
Section: Discussionmentioning
confidence: 99%